Species composition of the family Ampullariidae Gray, 1824 in Vietnam - Thanh, Dang Ngoc; Hai, Ho Thanh; Cuong, Duong Ngoc (Academia Journal of Biology, 2015)
The family Ampullariidae includes species with the biggest size among freshwater snails, characterized for tropical waters. Based on analysis of samples collected from many locations in Vietnam, 5 species (Pila polita, P. conica, P. ampullacea, Pomacea canaliculata, P. bridgesi) belonging to 2 genera (Pila and Pomacea) of family Ampullariidae are determined. Key for identification of genera and species, description, distribution, and some remarks on taxonomy of these species are given also in this paper.